Estudio de prefactibilidad para la fabricación de abono a base de residuos sólidos orgánicos - Tarazona Tello, Ethel Jimena (2019)
Although the human being is responsible for producing a large amount of waste, it seems that sometimes we still refuse to recycle. The only thing we achieve is to damage the place we live in and therefore ourselves. One of the actions, part of sustainable development is recycling, which allows us to provide our future generations with a green and blue planet. This research seeks to explain the process of manufacturing fertilizer based on organic solid waste, as well as to promote the classification of waste for future reuse.